Evaluation of recombinant activated protein C therapy on the outcome of patients with severe sepsis and septic shock - Osama Samir Abdelgelil Kotb; Hassan Khaled Nagy; Khaled Hussien; Tamer Abdallah (Cairo : Osama Samir Abdelgelil Kotb, 2013)
In the study, there was no difference between the matched treated and matched untreated groups in days on vasopressors, days on mechanical ventilation, length of icu stay, and length of hospital stay in days, these findings are not surprising and are similar to those found in prowess and adress study . our study is limited in that it is a prospective and retrospective analysis and that the number of patients is relatively small finally
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Outcome of patients; Protein C; Septic shock